2021
DOI: 10.1155/2021/9960241
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes Containing LINC00636 Inhibit MAPK1 through the miR-450a-2-3p Overexpression in Human Pericardial Fluid and Improve Cardiac Fibrosis in Patients with Atrial Fibrillation

Abstract: The purpose of this study was to investigate the regulatory mechanism of miR-450a-2-3p in myocardial fibrosis in patients with atrial fibrillation. For this purpose, the expression profile of GSE55296 was extracted from the GEO database, and differentially expressed lncRNAs were identified. Gene ontology analysis of the target genes of mir-450a-2-3p indicated that there was a regulatory relationship between LINC00636 and miR-450a-2-3p. Further, the expression levels of the analyzed RNAs were confirmed by RT-qP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…[ 24 ] Liu et al proposed that the anti-fibrotic molecule LINC00636 could inhibit MAPK1 by promoting the overexpression of miR-450a-2-3p, which ultimately exerts an ameliorative effect on cardiac fibrosis in patients with atrial fibrillation. [ 25 ] Therefore, MAPK1 may be a potential therapeutic target for antifibrotic therapy. Src is a non-receptor tyrosine kinase that integrates multiple extracellular signals and is associated with several human fibrotic diseases by promoting STAT3 phosphorylation to drive fibroblast proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…[ 24 ] Liu et al proposed that the anti-fibrotic molecule LINC00636 could inhibit MAPK1 by promoting the overexpression of miR-450a-2-3p, which ultimately exerts an ameliorative effect on cardiac fibrosis in patients with atrial fibrillation. [ 25 ] Therefore, MAPK1 may be a potential therapeutic target for antifibrotic therapy. Src is a non-receptor tyrosine kinase that integrates multiple extracellular signals and is associated with several human fibrotic diseases by promoting STAT3 phosphorylation to drive fibroblast proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, lncRNA H19 expression is upregulated in cardiac fibrotic tissues and activated fibroblasts, while overexpression of DUSP5 abrogates the pro-proliferative effect of H19 in cardiac fibroblasts by a mechanism associated with inhibition of ERK1/2 phosphorylation ( Tao et al, 2016 ). In addition, MAPK1 has been reported to involve in various biological processes including myocardial fibrosis, and can be inhibited by exosomes containing LINC00636 by elevating the miR-450a-2-3p expression, thus alleviating the cardiac fibrosis in patients with AF ( Liu et al, 2021b ).…”
Section: Regulation Of Tgf-β/smad Signaling Pathway By Ncrnas In Card...mentioning
confidence: 99%
“…Interestingly, Liu et al demonstrated that AF patients presented decreased expression levels of EV-incorporated LINC00636 (Long Intergenic Non-Protein Coding RNA) and miR-450a-2-3p compared with non-AF patients. Moreover, the expression levels of these two RNAs positively correlated with each other [ 36 ]. Importantly, Chen et al proved that AF patients showed an increased expression of myocardial infarction associated transcript (MIAT) in serum-derived EVs when compared with healthy individuals.…”
Section: Extracellular Vesicles In Patients With Atrial Fibrillationmentioning
confidence: 99%